Risk factors of respiratory allergy in children with atopic dermatitis - Sjawitri P. Siregar; Bambang Madiyono; Amar W. Adisasmito (Indonesian Pediatric Society, 1999)
This paper described a case-control study among atopic dermatitis (AD)patients on the development of respiratoric allergy (RA) i.e., (asthma and for allergic rhinitis), in Cipto Mangunkusumo Hospital, Jakarta. Secondary data were collected from January 1, 1995 to April31, 1998. One hundred and one children with RAin AD patients (case group), and 101 children with AD (control group) aged <16 years were evaluated for exposure to possible risk factors for RA. The mean age of AD onset was 1 year and 5 weeks in the case group, and 2 years and 2 months in the control group (p = 0.000). Early AD onset < 1 year was a significant risk factor (p = 0,0003; OR = 9.6, 95% confid ence intervals 2.8 ; 33.3). History of inhalant allergy was associated with the excess risk for RAin children with AD (p = 0.0025; OR 2.9, 95%C!: 1.5; 5.7). Early onset of egg supplementation <6 months was statistically significant to increase that such risk (p = 0.05; OR 3.3, 95%CI: 1.0 ; 11.7). Our findings suggest that early onset of AD before the age of one year would increase the development of RA Qn AD patients. Besides, we conclude that postponing the administration of egg supplementation until the age of one year, and preventing the exposure of inhalant aJlergens would prevent RA, particularly in family history of a topy.